2021
DOI: 10.18053/jctres.07.202101.011
|View full text |Cite
|
Sign up to set email alerts
|

The current role of surgery and SBRT in early stage of small cell lung cancer

Abstract: Background: Early stage small cell lung cancer (T1-2N0M0SCLC) represents 7% of all SCLC. The standard treatment in patients with intrathoracic SCLC disease is the use of concurrent chemoradiotherapy (CRT). Nowadays, the recommended management of this highly selected group is surgical resection due to favorable survival outcomes. For medically inoperable patients or those who refuse surgery, there is an increasing interest in evaluating the role of Stereotactic Body Radiotherapy (SBRT) for T1-2N0SCLC, transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 132 publications
0
1
0
Order By: Relevance
“…In addition, those patients with early-stage SCLC treated by SBRT can also achieved a well-tolerated treatment with acceptable OS and excellent LC. Recently, there were an increasing of evidences for radiation oncologists to choose SBRT as reasonable treatment for patients with early-stage SCLC (34). Raj et al reported that for the patients with early-stage SCLC following SBRT, the 1-year and 2-year OS were 73.1% and 36.6%, respectively, and the 1-, 2-, and 3-year LC rates for the cohort were 100% (35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, those patients with early-stage SCLC treated by SBRT can also achieved a well-tolerated treatment with acceptable OS and excellent LC. Recently, there were an increasing of evidences for radiation oncologists to choose SBRT as reasonable treatment for patients with early-stage SCLC (34). Raj et al reported that for the patients with early-stage SCLC following SBRT, the 1-year and 2-year OS were 73.1% and 36.6%, respectively, and the 1-, 2-, and 3-year LC rates for the cohort were 100% (35).…”
Section: Discussionmentioning
confidence: 99%